’EUGEN EHRLICH LEBEN UND WERK DES BEGRÜNDERS DER RECHTSSOZIOLOGIE - REHBINDER, M. (Ehrlich’s Journal, 2023)
The main stages of Ehrlich’s life, his scientific and pedagogical activity are analysed. It is noted that the most important milestones of Ehrlich’s scientific work are “The Silent Will”, “The Foundations of Sociology of Law”, “The Legal Logic”. Much attention is paid to the Ehrlich’s work as a professor of Roman law in the Chernivtsi Law Center, as guest professor at Chicago, Harvard, Holland, Switzerland, and Romania. The reasons that caused Ehrlich to leave Chernivtsi University are revealed.